Legal framework relating to alternative dispute resolution in Belgian public law - Goes, Pieter (Mednarodna revija za javno upravo, 2014)
The application of alternative dispute resolution is increasing in Belgian administrative law hand in hand with the move towards a more bilateral relationship between administration and citizens, characterized by reciprocity and dialogue. The specific character of public law is the cause of specific legal problems and limitations. This paper examines these restrictions and their opportunities as a contribution to the creation of a theoretical framework for alternative dispute resolution in administrative law and serves in an international context as an overview of this theme.
Keywords: alternative dispute resolution; alternativno reševanje sporov; Belgija; Belgium; legal problems; pravni problemi; procedural administrative law; procesno pravo; upravno pravo